(untitled) (Boletin Médico de Postgrado, 2020)
Cardiovascular autonomic neuropathy in diabetic patients (CAN) is defined as a chronic complication of diabetes (DM) of the microangiopathic type, which is expressed as dysautonomia of the cardiovascular system. We performed an observational descriptive cross-sectional study to characterize clinically and epidemiologically type 2 diabetic patients with CAN that were attended in December 2014 at the Unidad de Diabetes of CCR-ASCARDIO in Barquisimeto, Lara state. The sample consisted of 68 type 2 diabetic patients with a prevalence of CAN according to the RINES VALCARDI (RV) test of 63.2%, by orthostatism of 45.6% and by the presence of inappropriate sinus tachycardia of 8.8%. In patients with CAN, there was female predominance and a greater percentage of patients had more than five years with diabetes and no metabolic control their disease. In conclusion, it is important to make an early diagnosis of diabetes and clearly identify symptoms that suggest dysautonomia in these patients.